Regulatory Fragmentation of Compensation and Recovery for Communities Affected by Mining Blasting: A Critical Normative Study of Cases in Leuwikaret, Lulut, and Hambalang - Saefullah Saefullah; Ajrina Rahmah Hira (Binamulia Hukum, 2026)
Mining blasting is a technically permissible activity in mining operations; however, it may generate ground vibrations, dust, noise, cracks in buildings, and disturbances to the comfort of surrounding communities. This article examines the regulatory fragmentation of compensation and recovery for communities affected by mining blasting, using limited empirical illustrations from Leuwikaret Village, Lulut Village, and Hambalang Village in Bogor Regency. This study employs a critical normative legal method, incorporating statutory, conceptual, and limited empirical-illustrative approaches. The findings indicate that environmental law regulates community rights, access to information, complaint mechanisms, compensation, recovery, supervision, and administrative sanctions. Mineral and coal mining law regulates good mining practices, reclamation, post-mining activities, guidance, supervision, data management, and community empowerment. Company law governs corporate social and environmental responsibility. However, these three legal regimes have not yet established specific operational mechanisms for verifying losses caused by blasting, disclosing technical blasting data, assessing damage to buildings, distinguishing corporate social responsibility from compensation, and defining the role of local governments in facilitating complaints. This article recommends the adoption of specific guidelines on compensation and recovery for losses arising from mining blasting.